Alkali-metal(Li, Na, and K)-adsorbed MoSi2N4 monolayer: an investigation of its outstanding electronic, optical, and photocatalytic properties. (1st January 2022) - Sun, Zhiyuan; Xu, Jing; Mwankemwa, Nsajigwa; Yang, Wenxing; Wu, Xianwen; Yi, Zao; Chen, Shanjun; Zhang, Weibin
Abstract: Single-layer MoSi2 N4, a high-quality two-dimensional material, has recently been fabricated by chemical vapor deposition. Motivated by this latest experimental work, herein, we apply first principles calculations to investigate the electronic, optical, and photocatalytic properties of alkali-metal(Li, Na, and K)-adsorbed MoSi2 N4 monolayer. The electronic structure analysis shows that pristine MoSi2 N4 monolayer exhibits an indirect bandgap ( E g = 1.89 eV). By contrast, the bandgaps of one Li-, Na-, and K-adsorbed MoSi2 N4 monolayer are 1.73 eV, 1.61 eV, and 1.75 eV, respectively. Moreover, the work function of MoSi2 N4 monolayer (4.80 eV) is significantly reduced after the adsorption of alkali metal atoms. The work functions of one Li-, Na-, and K-adsorbed MoSi2 N4 monolayer are 1.50 eV, 1.43 eV, and 2.03 eV, respectively. Then, optical investigations indicate that alkali metal adsorption processes substantially increase the visible light absorption range and coefficient of MoSi2 N4 monolayer. Furthermore, based on redox potential variations after alkali metals are adsorbed, Li- and Na-adsorbed MoSi2 N4 monolayers are more suitable for the water splitting photocatalytic process, and the Li-adsorbed case shows the highest potential application for CO2 reduction. In conclusion, alkali-metal-adsorbed MoSi2 N4 monolayer exhibits promising applications as novel optoelectronic devices and photocatalytic materials due to its unique physical and chemical properties.